Aplikasi E-Commerce Nusantara Culinary Berbasis Website - Eunike Charina Ibrena Tarigan; Setia Mangiring Marpaung; Wetina Hulu; Rani Rosalinda (Cattleya Darmaya Fortuna, 2025)
This study aims to develop a web-based e-commerce system to support the digital transformation of culinary Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Many culinary businesses still rely on conventional sales methods, resulting in limited market reach, inefficient transaction processes, and poor data management. Therefore, an integrated and user-friendly system is required to enhance business competitiveness in the digital era. This research adopts the Agile Software Development methodology, which includes planning, system design, implementation, testing, and evaluation stages. The system is developed using web technologies, including a programming language, database management system, and responsive user interface framework. The platform provides key features such as product management, online transactions, communication between sellers and buyers, and administrative control. The results indicate that the developed system improves the efficiency of transaction processes, expands market access, and enhances product promotion. The system also offers a user-friendly interface that simplifies user interaction, particularly for MSME actors with limited technical expertise. Based on black box testing, all system functionalities operate as expected. In conclusion, the proposed system effectively supports the digitalization of culinary MSMEs by improving operational efficiency and accessibility. This study contributes to the development of integrated digital platforms that strengthen the competitiveness of local culinary products. Future research can focus on mobile integration and advanced recommendation features.